CYP3A4 기질과 억제제 약물의 병용 고령환자에서 횡문근융해증 부작용 연관성 - 장준혁; 추은정; 박래웅; 이숙향 (약물역학위해관리학회지, 2023)
Drug-induced rhabdomyolysis can cause acute kidney injury and rate of polypharmacy is high in the elderly. This study aimed to assess the incidence of rhabdomyolysis with combination therapy of CYP3A4 substrates (S) and inhibitors (I) in the elderly in Korea. Methods: Patients were selected from the 2017 elderly patient data (the Korean Health Insurance Review and Assessment Service - Aged Population Sample). The list of CYP3A4 S and I was taken from the Indiana university of pharmacy and converted to Korean ATC codes. Further selection criteria were a medication possession ratio greater than 80%, duration of medication 7 days or longer, and duration of follow-up 3 months or longer. The incidence and odds ratio of rhabdomyolysis with top 50 pairs of the combination of drugs were assessed. Comparative analysis of the association of rhabdomyolysis with patient characteristics and comorbidities was analyzed using Chi-square test. Logistic regression models were used to analyze the association with rhabdomyolysis for each variable. Results: Rhabdomyolysis was identified in 78 cases in 24,240 patients with 7 days or longer use (DC7), and 19 cases in 3,444 patients with 30 days or longer use (DC30) of CYP3A4 S and I. The comorbidities of severe liver disease and rheumatoid disease had a significant association. Among patients with DC7, the drug pairs (S,I) with significant adjusted odds ratio (aOR) were [clopidogrel, cimetidine] (0.32; 95% CI, 0.10–0.96). Among patients with DC30, the drug pairs with significant aOR were [atorvastatin and fluconazole] (16.13; 95% CI, 2.40–108.36), [alprazolam and amiodarone] (10.74; 95% CI, 1.62–71.38), [zolpidem tartrate and ciprofloxacin] (9.61; 95% CI, 1.38–66.83), [lansoprazole and amiodarone] (7.51; 95% CI, 1.04–54.23). Conclusion: In the elderly, the combination uses of CYP3A4 substrate and inhibitor with 30 days or longer use of atorvastatin and fluconazole had the highest risk of rhabdomyolysis with risk factors of comorbidities of liver disease or rheumatoid disease.
Keywords: Rhabdomyolysis; Drug interaction; CYP3A4 substrate; CYP3A4 inhibitor